Effect of localization, length and orientation of chondrocytic primary cilium on murine growth plate organization - Ascenzi, Maria-Grazia (2011)
The research investigates the role of the immotile chondrocytic primary cilium in the growth plate. This study was motivated by (i) the recent evidence of the mechano-sensorial function of the primary cilium in kidney tubule epithelial cells; and (ii) the distinct three-dimensional orientation patterns that the chondrocytic primary cilium forms in articular cartilage in the presence or the absence of loading. For our investigation, we used the Smad1/5(CKO) mutant mouse, whose disorganized growth plate is due to the conditional deletion of Smad 1 and 5 proteins that also affect the so-called Indian Hedgehog pathway, whose physical and functional topography has been shown to be partially controlled by the primary cilium. Fluorescence and confocal microscopy on stained sections visualized ciliated chondrocytes. Morphometric data regarding position, orientation and eccentricity of chondrocytes, and ciliary localization on cell membrane, length and orientation, were collected and reconstructed from images. We established that both localization and orientation of the cilium are definite, and differently so, in the Smad1/5(CKO) and control mice. The orientation of the primary cilium, relative to the major axis of the chondrocyte, clusters at 80° with respect to the anterior-posterior direction for the Smad1/5(CKO) mice, showing loss of the additional clustering present in the control mice at 10°. We therefore hypothesized that the clustering at 10° contains information of columnar organization. To test our hypothesis, we prepared a mathematical model of relative positioning of the proliferative chondrocytic population based on ciliary orientation. Our model belongs to the category of “interactive particle system models for self-organization with birth”. The model qualitatively reproduced the experimentally observed chondrocytic arrangements in growth plate of each of the Smad1/5(CKO) and control mice. Our mathematically predicted cell division process will need to be observed experimentally to advance the identification of ciliary function in the growth plate.